Adiponectin alleviated Alzheimer‐like pathologies via autophagy‐lysosomal activation. Issue 12 (14th November 2021) - He, Kaiwu; Nie, Lulin; Ali, Tahir; Wang, Shujin; Chen, Xiao; Liu, Zizhen; Li, Weifen; Zhang, Kaiqin; Xu, Jia; Liu, Jianjun; Yu, Zhi‐Jian; Yang, Xifei; et al.
Abstract: Adiponectin (APN) deficiency has also been associated with Alzheimer‐like pathologies. Recent studies have illuminated the importance of APN signaling in reducing Aβ accumulation, and the Aβ elimination mechanism remains rudimentary. Therefore, we aimed to elucidate the APN role in reducing Aβ accumulation and its associated abnormalities by targeting autophagy and lysosomal protein changes. To assess, we performed a combined pharmacological and genetic approach while using preclinical models and human samples. Our results demonstrated that the APN level significantly diminished in the plasma of patients with dementia and 5xFAD mice (6 months old), which positively correlated with Mini‐Mental State Examination (MMSE), and negatively correlated with Clinical Dementia Rating (CDR), respectively. APN deficiency accelerated cognitive impairment, Aβ deposition, and neuroinflammation in 5xFAD mice (5xFAD*APN KO), which was significantly rescued by AdipoRon (AR) treatment. Furthermore, AR treatment also markedly reduced Aβ deposition and attenuated neuroinflammation in APP/PS1 mice without altering APP expression and processing. Interestingly, AR treatment triggered autophagy by mediating AMPK‐mTOR pathway signaling. Most importantly, APN deficiency dysregulated lysosomal enzymes level, which was recovered by AR administration. We further validated these changes by proteomic analysis. These findings reveal that APN is the negative regulator of Aβ deposition and its associated pathophysiologies. To eliminate Aβ both extra‐ and intracellular deposition, APN contributes via the autophagic/lysosomal pathway. It presents a therapeutic avenue for AD therapy by targeting autophagic and lysosomal signaling. Abstract : Our study revealed that adiponectin (APN) deficiency accelerates Aβ deposition, neuroinflammation, and cognitive behaviors impairments. However, AdipoRon treatment could reverse these pathological changes. Further molecular studies show APN contributes to AD‐like deficits via the autophagy‐lysosomal pathway. Thus, APN is the negative regulator of Aβ deposition and its associated pathologies.